Thar Kranti: a new jamun variety - Singh, Sanjay; Singh, A K; Rao, V V Appa; Bhargawa, R; Sharma, B D (Indian Horticulture, 2019)
Jamun selection, Thar Kranti, was developed at Central Horticultural Experiment Station, Vejalpur (Godhra), Gujarat, and released by Central Institute for Arid Horticulture, Bikaner in 2016. This selection was identified and selected on the basis of its elite horticultural traits. The selection outperformed in flowering, fruiting behaviour and fruit quality attributes under semi-arid ecosystem of western India.